PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUDIO-VISUAL MENGGUNAKAN POWTOON UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA DI SMP NEGERI METAMAUK - Hane, Yovita Berek; Fallo, Diana Y. A.; Neno, Khatrin J, Taku (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The objective of this study was to develop a proper audio-visual learning media using Powtoon application and determine its effectiveness in improving students’ learning interest in Informatics subject at SMP Negeri Metamauk. The research method used was Research and Development (R&D) with the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects included two validators (media expert and material expert) and 42 Grade VIII students. Data collection instruments were validation sheets and student response questionnaires, analyzed using descriptive percentage statistics. The results showed that: (1) The audio-visual learning media using Powtoon was successfully developed following the ADDIE model; (2) Media expert validation obtained 93.33% and material expert validation also 93.33%, both categorized as Very Feasible; and (3) Overall student responses reached 91.27%, categorized as Very Good, consisting of learning interest 91.67%, Powtoon feature implementation 90.48%, and material mastery 91.67%. In conclusion, the developed Powtoon learning media met the feasibility criteria and was proven effective in improving students’ learning interest in Informatics subject.